OVINE SEMEN CRYOPRESERVATION USING THREE EXTENDERS AND FOUR COMBINATIONS OF PERMEANT AND NON PERMEANT AGENTS - Sandoval M., Rocío (2007)
The objective of the study was to evaluate the effect of three extenders and four combinations of two permeant and two non permeant cryoprotectant agents on the quality of post thaw ram semen. In Experiment 1, three extender were evaluated (A, B, and C) in order to select the best for the next step. In Experiment 2, different combinations of cryoprotectant agents were evaluated as follow: 1) Glycerol–Trehalose, 2) Glycerol– Sucrose, 3) Ethylene glycol-Trehalose, and 4) Ethylene glycol–Sucrose. In experiment 1, motility, viability and acrosomal integrity in extender A were higher than in extender B and extender C, and therefore, extender A was used for experiment 2. In this assay, motility, viability and acrosomal integrity, thermoresistance, and plasmatic membrane integrity were higher in groups Glycerol-sucrose and Glycerol-trehalose in comparison with groups Ethilene glycol-sucrose and Ethilene glycol-trehalose. However, there were not significative differences between sucrose or trehalose. In conclusion, an extender with characteristics of extender A using glycerol plus trehalose or sucrose constitute a good alternative for cryopreservation of ram semen.